Uso do Ciprofloxacino em diferentes doses incorporado em dispositivo de quitosana na prevenção da infecção em modelo de fraturas expostas em ratos - Silvia Iovine Kobata (2017)
Open fractures are mainly caused by high-energy accidents. Osteomyelitis are the most common complication from open fractures and its treatment involves surgical treatment and high doses of systemic antibiotics. Despite all medical and pharmacological advances, infection rates after open fractures has not changed in the past 20 years, promoting high social and economic costs. A bio absorbable carrier for ciprofloxacin could prevent the need for additional surgical procedure when impregnated at osteo-fixation device; however, the exact concentration of ciprofloxacin that would prevent infection at the open fracture site remains controversial. Objective. Evaluate efficiency of local delivery treatment using different concentrations of ciprofloxacin incorporated at the fixation device using quitosana as carrier, a bio absorbable polymer, in order to prevent infection after open fracture contaminated with S. aureus in rats. Methods. 52 Wistar rats underwent to an established S aureus contaminated fracture model. All animals assigned to one of six groups after one hour of bacterial contamination. Group A underwent to fracture fixation using K-wire but no antibiotic treatment (control group). Group B after fracture fixation with K-wire had systemic ciprofloxacin treatment. Group C underwent to fracture fixation using K-wire impregnated with quitosana only. Group D had fracture fixation using K-wire with quitosana and 10% ciprofloxacin impregnated. Group E underwent to fracture fixation using K-wire with quitosana and 25% ciprofloxacin impregnated, and group F had fracture fixation using K-wire with quitosana and 50% ciprofloxacin impregnated. After 4 weeks, all animals underwent to an established 99mTc-ceftizoxima scintigraphy evaluation, callus formation measurement and histological analysis. ANOVA, t-Student and Kruskal Wallis were used for quantitative variables statistical analysis, whereas qui square and exact Fisher were used for qualitative variables. Results. Treatment using 25% and 50% of ciprofloxacin incorporated at the fracture fixation device were effective in preventing bone infection compared to control group (p<0,05). Quitosana were not effective in preventing bone infection when used alone compared to control group (p>0,05). Histological findings demonstrated bone-healing delay with 50% of ciprofloxacin treatment. However, no difference in callus formation measurement were observed between groups (p>0,05). Conclusion. Local delivery treatment for contaminated open fracture with Staphylococcus aureus using a bio absorbable polymer with ciprofloxacin impregnated is effective when ciprofloxacin concentration is above 25% in rats.